Design optimisation of high-brightness laser diodes for external cavity operation in the BRIDLE project - Larkins, E.C.; Bull, S.; Kaunga-Nyirenda, S.; Helal, M.A.; Vilokkinen, V.; Uusimaa, P.; Crump, P.; Erbert, G. (2014)
We report on the design aspects of high performance diode lasers for application in high-brightness spectral beam combining and coherent beam combining modules. Key performance trade-offs are identified and potential solutions are explored.